Effect of finishing and polishing on color stability of a nanofilled resin immersed in different media - Ana Luísa Botta Martins de OLIVEIRA; Camila Cruz LORENZETTI; Patrícia Petromilli Nordi Sasso GARCIA; Elisa Maria Aparecida GIRO
OBJECTIVE: The purpose of this study was to evaluate the effect of finishing and polishing on color stability of a nanofilled composite resin (Filtek Z350 XT) according to different immersion media.MATERIAL AND METHOD: Composite disks (10 mm diameter, 2 mm thickness) were prepared for each group (n = 6) using a stainless steel mold. The groups were divided according to the presence or absence of finishing and polishing procedure and immersion media (artificial saliva, artificial juice- KAPO(r) Coca-Cola(r)flavors: pineapple, orange, strawberry and grape). The finishing and polishing procedures were performed using Super -Snap(r) disks. The specimens were stored in artificial saliva for 24 hours (baseline) and were analyzed using a color spectrophotometer by CIELab system. Then, they were immersed in different media for 5 minutes, 3 times a day, every 4 hours during 60 days. They were stored in artificial saliva at 37 ± 1°C during the immersion intervals. After this time, new measure of color was performed. The data were analyzed using Kruskall-Wallis test and Mann- Whitney test. The significance level was 5%.RESULT: The results showed that the finishing/polishing not significantly influence the color stability of resin composite (p > 0.05). There was no statistically significant difference in the color stability of the studied resin after immersion in different media (p > 0.05).CONCLUSION: The finishing and polishing procedures and the immersion media did not have influence on color stability of nanofilled resin Filtek Z350 XT.